Tratamento de efluente de galvanoplastia empregando membranas poliméricas de troca iônica - Gonçalves, Bruna Cristina (2019)
The objective of this work was to prepare ionic exchange polymer membranes and apply them to the treatment of nickel plating effluent. For this purpose, blends with polyethersulfone (PES), polysulfone (PSU), NaCl dissolved in N'N- dimethylformamide (DMF) and containing cationic resin Purolite (RP), were prepared by the phase inversion technique of variability the evaporation time of the solvent (te 0 and 60 s) and the temperature of the non-solvent (Tnon-solvent 25 and 40°C). As membranes were characterized morphologically in terms of Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Differential Exploration Calorimetry (DSC), hydrophilicity parameters and pHzpc. The permeability tests with the effluent were reached on a dead-end filtration cell, as well as the percentage of scale. The kinetics and equilibrium isotherms with a solution of nickel (40 mg L-1) were determined with the RP, aiming at a linear solution of data on the number of cases, with the objective of evaluating compliance of the current legislation. The results were that blends prepared with te 60s and Tnon-solvent 40°C had an increase in permeate flux. Furthermore, membranes produced without NaCl in the composition and/or with insertion of DMF in the coagulation bath were the ones with the best removal of the metal ions present in the effluent. The morphological and dynamic characterizations showed that the ion exchange membranes showed higher hydrophilicity, permeate flow and lower thermal stability when compared to the control blends. Under the conditions specified in the preparation of the membranes, SEM images showed that all membranes are asymmetric. The resin insertion caused a pHzpc of 2.2, differently from the control membrane, thus favoring the treatment of effluents containing ions because the surface of the blende was negatively charged. The tests carried out in the filtration cell showed that the cationic blends must be positioned in such a way that the RP is in direct contact with the effluent inside the module. The Sips isotherm demonstrated that it is necessary to insert 2,2g of RP on the blend. The ion exchange blends achieved average reductions of 90, 80, 95 and 90% Ni, Fe, Cu and Cr ions respectively, as well as 50% of the organic effluent load, with a mean fouling index of 70%. The flow of the blends was reestablished after permeation of the effluent. In this way, the ion exchange membranes produced in this work can be used in the treatment of electroplating nickel plating.